PEMBERDAYAAN KADER KESEHATAN DALAM DETEKSI DINI KESEIMBANGAN TUBUH PADA LANSIA DI PUSKESMAS SARIJADI KECAMATAN SUKASARI KOTA BANDUNG (Poltekkes Kemenkes Bandung, 2023)
The aging process is usually associated with a decrease in a person's physical and mental condition which is marked by a progressive decline in perceptual, motoric, cognitive, and memory functions. This condition is usually experienced by someone with old age. The existence of physical and mental disorders in the elderly raises problems, which are a disturbance of body balance and the risk of falling. One of the efforts to improve the quality of life of the elderly is by understanding and early detection of body balance in the elderly based on community empowerment in an effort to prevent the risk of falling, which is empowering elderly health cadres. This activity aims to increase the knowledge and skills of health cadres regarding early detection of body balance in the elderly. The method of this community service activity is lectures, discussions, questions and answers, and demonstration. There was an increase in the knowledge of elderly health cadres about early detection of body balance in the elderly, from 48.7 to 62.7 from before and after the training, which of of 14 points. In addition, there was a fairly high increase from 45 to 71 from before and after the training, which of 26 points. The conclusion was that there was an increase in the knowledge and skills of health cadres regarding early detection of body balance in the elderly.